Comparative effects of different types of exercise on health-related quality of life during and after active cancer treatment: A systematic review and network meta-analysis - Vicente Martínez-Vizcaíno; Iván Cavero-Redondo; Sara Reina-Gutiérrez; Luis Gracia-Marco; José J. Gil-Cosano; Bruno Bizzozero-Peroni; Fernando Rodriguez-Artalejo; Esther Ubago-Guisado (Elsevier, 2023)
Background: The positive influence of most types of exercise has been reported repeatedly, but what the most effective exercise approaches are for improving health-related quality of life (HRQoL) in people with cancer remains unknown. The aim of this systematic review and network meta-analysis was to synthesize the evidence from intervention studies to assess the effects of different types of exercise on HRQoL during and after cancer treatment. Methods: MEDLINE, SPORTDiscus, the Cochrane Library, Web of Science, and Scopus were searched for randomized controlled trials aimed at testing the effects of exercise interventions meant to improve HRQoL in people with cancer. Separate analyses were conducted for HRQoL as measured by general and cancer-specific questionnaires. We also evaluated whether the effects of exercise were different during and after cancer treatment in both the physical and mental HRQoL domains. Results: In total, 93 studies involving 7435 people with cancer were included. Network effect size estimates comparing exercise intervention vs. usual care were significant for combined exercise (0.35, 95% confidence interval (95%CI): 0.14-0.56) for HRQoL as measured by general questionnaires, and for combined (0.31, 95%CI: 0.13-0.48), mind-body exercise (0.54, 95%CI: 0.18-0.89), and walking (0.39, 95%CI: 0.04-0.74) for HRQoL as measured by cancer-specific questionnaires. Conclusion: Exercise programs combining aerobic and resistance training can be recommended to improve HRQoL during and after cancer treatment. The scarcity and heterogeneity of these studies prevents us from making recommendations about other exercise modalities due to insufficient evidence.